eBook Service in Shanghai Library - Qing Zhou (International Journal of Librarianship (IJoL), 2016)
In the 21st century, with the rapid development of mobile Internet, people's reading habits have started shifting from the traditional paper-based media, to completely new media such as cell phones, eBook readers, tablet PCs and so on. "Shanghai Library’s Urban Digital Reading Service Platform" integrates all types of collections of digital resources to support eBook readers, tablet PCs, smart phones and other types ofmobiledevices. Thisplatformprovidesaconvenient,low-costandfriendlylearninginterfacetoonline users, providing one of the best reading experiences. This also creates a one-stop public library reading platform, and meets the reader’s need for reading on the go. By investigating and researching libraries’ experiences and requirements for digital reading platforms and its internationalization service, this paper will discuss its further development.